Formation of readiness of future occupational therapists to use modern rehabilitation technologies in profession - Donchenko, Viktoriia; Zhamardiy, Valeriy; Shkola, Olena; Fomenko, Olena; Khlus, Nataliia; Kabatska, Olena; Heta, Alla (My University, 2024)
Aim: The aim of the study is to determine, substantiate and experimentally test the effectiveness of proposed didactic conditions for the formation of readiness of future occupational therapists to use modern rehabilitation technologies in professional activities. Materials and Methods: The program of the local pedagogical experiment was implemented through the realization of ascertaining (2022–2023) and formative (2023–2024) stages. Pedagogical experiment involved students in the specialty 227 Therapy and Rehabilitation, field of knowledge 22 Health care of the Poltava State Medical University (Ukraine). Results: The analysis of the results of the formative experiment, during which students studied according to the implementation program in the system of professional training in a medical institution of higher education under specified didactic conditions, shows positive changes in the levels of readiness of future occupational therapists to use modern rehabilitation technologies in professional activities. Conclusions: The model proposed by the authors of forming the readiness of future occupational therapists to use modern rehabilitation technologies in professional activities improves the quality of education of occupational therapists and better prepares them for practical activities
Formation of readiness of future occupational therapists to use modern rehabilitation technologies in profession / Viktoriia Donchenko, Valeriy Zhamardiy, Olena Shkola, Olena Fomenko, Nataliia Khlus, Olena Kabatska, Alla Heta // Acta Balneologica. Journal of the polish balneology and physical medicine association. Aluna Publishing, 2024. – Vol. LXVI. – Issue 6 (184). – P. 392–399
Keywords: health, readiness, occupational therapists, rehabilitation technologies, professional activities, patients; здоров'я, готовність, ерготерапевти, реабілітаційні технології, професійна діяльність, пацієнти